Raman microspectroscopy for microbiology - Lee, Kang Soo; Landry, Zachary; Pereira, Fatima C.; Wagner, Michael; Berry, David; Huang, Wei E.; Taylor, Gordon T.; Kneipp, Janina; Popp, Jürgen; Zhang, Meng; Cheng, Ji-Xin; Stocker, Roman (Nature Reviews Methods Primers, 2021)
Raman microspectroscopy offers microbiologists a rapid and non-destructive technique to assess the chemical composition of individual live microorganisms in near real time. In this Primer, we outline the methodology and potential for its application to microbiology. We describe the technical aspects of Raman analyses and practical approaches to apply this method to microbiological questions. We discuss recent and potential future applications to determine the composition and distribution of microbial metabolites down to subcellular scale; to investigate the host–microorganism, cell–cell and cell–environment molecular exchanges that underlie the structure of microbial ecosystems from the ocean to the human gut microbiomes; and to interrogate the microbial diversity of functional roles in environmental and industrial processes — key themes in modern microbiology. We describe the current technical limitations of Raman microspectroscopy for investigation of microorganisms and approaches to minimize or address them. Recent technological innovations in Raman microspectroscopy will further reinforce the power and capacity of this method for broader adoptions in microbiology, allowing microbiologists to deepen their understanding of the microbial ecology of complex communities at nearly any scale of interest.
CRIS-Team Scopus Importer:2023-04-20